6. SISTEM PEMILIHAN ANGGOTA DPR (BUNDESTAG) DI JERMAN SERTA PELAJARAN YANG DAPAT DIAMBIL INDONESIA. - Utomo, Tri Cahyo (Faculty of Social and Political Sciences Diponegoro University, 2008)
The electoral system for members of the House of Representatives in Indonesia is criticized. It is considered as unjust and unrepresentative.Accordingly, Indonesia should follow the electoral system for members of Bundes Germany, that is â€œMixed Member Proportional Systemâ€.